2021
DOI: 10.3389/fcell.2021.662780
|View full text |Cite
|
Sign up to set email alerts
|

SP1-Mediated Upregulation of Long Noncoding RNA ZFAS1 Involved in Non-syndromic Cleft Lip and Palate via Inactivating WNT/β-Catenin Signaling Pathway

Abstract: Non-syndromic cleft lip and palate (NSCLP) is one of the most common congenital malformations with multifactorial etiology. Although long non-coding RNAs (lncRNAs) have been implicated in the development of lip and palate, their roles in NSCLP are not fully elucidated. This study aimed to investigate how dysregulated lncRNAs contribute to NSCLP. Using lncRNA sequencing, bioinformatics analysis, and clinical tissue sample detection, we identified that lncRNA ZFAS1 was significantly upregulated in NSCLP. The upr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Meanwhile, miRNA‐binding site exists in some specific lncRNAs that control lncRNA and forward gene expression (Q. Liu et al, 2018). This might explain the SP1 differences in previous research, the predicted hsa‐miR‐1224‐3p in intermediate regulatory network might account for this opposite finding (Chen et al, 2021). Few studies have investigated hsa‐miR‐1224‐3p.…”
Section: Discussionmentioning
confidence: 76%
“…Meanwhile, miRNA‐binding site exists in some specific lncRNAs that control lncRNA and forward gene expression (Q. Liu et al, 2018). This might explain the SP1 differences in previous research, the predicted hsa‐miR‐1224‐3p in intermediate regulatory network might account for this opposite finding (Chen et al, 2021). Few studies have investigated hsa‐miR‐1224‐3p.…”
Section: Discussionmentioning
confidence: 76%
“…We next extended the analysis on binding transcription factors and found that risk-eSNPs were statistically significantly enriched in transcription factor binding sites, such as CHD1, GATA6, KDM4A, CTCF, TBP, E2F6, SP1, NANOG, YY1, and RAD21 ( Figure 2 C). Many of these transcription factors have been shown to be important in lip development or NSCL/P [ 22 , 23 , 24 , 25 , 26 ]. In addition, the eSNP-TF-eGene regulatory relationships for the top five TFs are listed in Table S5 .…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, our studies showed that LINC01608 was overexpressed in HCC and functioned as a ceRNA for miR‐875‐5p to promote HCC progression. Additionally, recent studies had demonstrated that some transcriptional factors, such as SP1 and MYBL2, could combine with the promoter of LncRNAs and regulate their expression 24,25 . YY1 is a transcriptional factor ubiquitously expressed in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recent studies had demonstrated that some transcriptional factors, such as SP1 and MYBL2, could combine with the promoter of LncRNAs and regulate their expression. 24,25 YY1 is a transcriptional factor ubiquitously expressed in mammalian cells. Previously published studies had indicated that YY1 could act as a transcriptional activator or a repressor and play important roles in several cancers.…”
Section: Discussionmentioning
confidence: 99%